Wild Fires and Climate Change: Health, Air Quality, Wild Fires and Causes in India - Yara EzAl Deen Sultan; Kanni Raj Arumugam Pillai (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Wildfires are a serious problem that affects wildlife all over the world which is human beings together with nature, both play a fundamental role in the cause of wildfires. Wildfires may start quite inconspicuously, but can rapidly accelerate to become fierce and uncontrollable, at which point they also pose serious health problems to humankind. To clarify this problem descriptive method was applied which described the basic issue and explained all outcomes accurately and clearly. So, the review illustrates that from an anthropological perspective, greater numbers of people are now living closer to forests (and rural areas in general), which although seemingly satisfactory and beneficial to them, has also led to an increase in the destruction of forests, due to intentionally, and unintentionally generated fires. In addition to the human impact, climate change and other natural phenomena are also destroying the forests. This review indicates the connection between wildfires and climate change, it also studies the effects of wildfires on health and air quality, in addition, the paper highlights the particularly challenging situation in India, which, due to its substantial share of global forestland, is proportionately more impacted by these fires. Besides, the review mentioned the analytical method to predict fire propagation.